2022
DOI: 10.46497/archrheumatol.2022.9247
|View full text |Cite
|
Sign up to set email alerts
|

Role of low-density lipoprotein receptor rs5925 (1959C>T) gene polymorphism in pathogenesis of dyslipidemia among Egyptian lupus nephritis patients

Abstract: Objectives: This study aims to investigate the prevalence of low-density lipoprotein receptor (LDL-R) rs5925 genetic variants and to evaluate their relationship with plasma lipid and kidney functions in lupus nephritis patients. Patients and methods: Between September 2020 and June 2021, a total of 100 lupus nephritis patients (8 males, 92 females; mean age: 31.1±1.1 years; range, 20 to 67 years) and a total of 100 age- and sex-matched healthy volunteers (10 males, 90 females; mean age: 35.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…Individuals carrying the C allele presented higher serum levels of LDL-C, TC, and TG compared to the TT homozygotes [17]. Meanwhile, the frequency of the LDLR rs5925 variant differs between the Chinese population and others [18][19][20]. Furthermore, studies have revealed that LDLR is also related to mood disorders.…”
Section: Introductionmentioning
confidence: 98%
“…Individuals carrying the C allele presented higher serum levels of LDL-C, TC, and TG compared to the TT homozygotes [17]. Meanwhile, the frequency of the LDLR rs5925 variant differs between the Chinese population and others [18][19][20]. Furthermore, studies have revealed that LDLR is also related to mood disorders.…”
Section: Introductionmentioning
confidence: 98%